2018
DOI: 10.1039/c8cp01898g
|View full text |Cite
|
Sign up to set email alerts
|

Shifted equilibria of organic acids and bases in the aqueous surface region

Abstract: Revealing the delicate balance between protonation/deprotonation and surface/bulk partitioning of organic acids and bases in aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(82 citation statements)
references
References 51 publications
4
78
0
Order By: Relevance
“…For example, although surface tension on the molecular level is reduced by the adsorption of surface-active species in the surface, the specic relation between surface tension and surface composition is typically unknown. 16,17 The response in surface tension is therefore instead related to variations in the bulk composition via the gradient between bulk and surface compositions. For macroscopic solutions, this relation is readily established, because the bulk composition is practically identical to the total composition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although surface tension on the molecular level is reduced by the adsorption of surface-active species in the surface, the specic relation between surface tension and surface composition is typically unknown. 16,17 The response in surface tension is therefore instead related to variations in the bulk composition via the gradient between bulk and surface compositions. For macroscopic solutions, this relation is readily established, because the bulk composition is practically identical to the total composition.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the “surface p K a ” cannot be directly obtained from the ratio of the surface deprotonated versus surface protonated species as calculated in the bulk either, because this ratio on the surface is not directly connected with the acid dissociation process but instead by differences in the equilibrium partitioning of the different forms (protonated and deprotonated) to the surface. 31 33 However, the fact that this data can be explained without needing a “surface p K a ” term does not exclude the possibility that surface dissociation occurs. Next, we will briefly review some previous studies on surface p K a and then show how a computational method can be employed to understand the energetics of acids at the air/water interface.…”
Section: Resultsmentioning
confidence: 93%
“…There have been studies which stated that the acid dissociation of surfactants at the interface cannot be directly quantified by the surface concentrations of the protonated and deprotonated forms as they are coupled with the adsorption processes. 31 33 Therefore, molecular dynamics (MD) simulations and free energy perturbation (FEP) calculations were performed to directly investigate the surface stability and free energy differences of protonation for the surface versus bulk acids. Since MD can resolve chemical systems at a molecular level and on a nanosecond timescale, it remains an essential tool for understanding chemical properties not readily obtained by experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown unique features of surfaces, compared to the bulk phase, for systems of atmospherically relevant composition (e.g. Werner et al, 2018, and references therein). We therefore anticipate that the ability to directly probe aerosol surfaces with high sensitivity and chemical selectivity will enable new studies of surface specific processes and chemical properties with atmospheric significance.…”
Section: Reviewer #2mentioning
confidence: 99%
“…Cosman et al, 2008;Park et al, 2009;Roy et al, 2020). The acidity of organic acids on water surfaces has been measured to be much lower than predicted for the bulk aqueous phase (Enami et al, 2010;Werner et al, 2018). The presence of surface-active organic molecules on droplet surfaces can affect droplet surface tension (Shulman et al, 1996;Bzdek et al, 2020) and morphology (Kwamena et al, 2010) that affect both warm (Sareen et al, 2013;Ovadnevaite et al, 2017) and ice cloud nucleation (Knopf and Forrester, 2011;Perkins et al, 2020).…”
Section: Reviewer #2mentioning
confidence: 99%